KORELASI ANTARA TINGKAT STIGMA DAN UPAYA NORMALISASI STIGMA OLEH OKNUM PEMUKA AGAMA YANG MENJADI PELAKU KEKERASAN SEKSUAL - Nuril Endi Rahman; Mohtar Mas'od; Muhad Fatoni (Jurnal Analisa Sosiologi, 2024)
This study aims to examine the correlation between the level of stigma and efforts to normalize stigma by religious leaders who become perpetrators of sexual violence. The rise of sexual violence cases that has been difficult to reveal, because the perpetrators use the “mask religion” so as to trick the wider community. The object of this research is the phenomenon of sexual violence commited by unscrupulous religious leaders. This research uses a quantitative approach of cross-sectional survey type, which uses bivariate analysis. The study respondents totalled 100 people, who live arround religious areas such as Islamic boarding schools, mosques, churches, monasteries, and other religious environments. Based on the Pearson correlation test, the result is 0.001, which means that there is a significant correlation between the high level of stigma given by the community to individual religious leaders who become perpetrators of sexual violence that the high level of stigma also reduces the successful normalization efforts carried out by the perpetrators. The perpetrators of sexual violence failed to use “religious masks”, so they still received a negative stigma and this stigma was a form of social sanction against the perpetrators. Efforts to normalize stigma were not successful, as well as a form of negation of the attitude of victim blaming, namely blaming the victim, as has happened in many cases. Thus sexual violence perpetrated by evil religious leaders is a form of moral degradation.